MEKTEPKE SHEKEMGI JASTAǴÍ ORTA TOPAR BALALARDÍŃ LEKSIKALÍQ BIRLIKLERDI ÓZLESTIRIW DINAMIKASÍ - Aymbetova, D. (SCIENCE and SOCIETY, 2024)
The article notes that the lexical repertoire of children of middle preschool age is twice as high as that of younger children, and this is very important information in creating innovative areas of children’s language research.